EXPLORING CHALLENGES OF DIFFERENTIATED INSTRUCTION IN ENGLISH FOREIGN LANGUAGE CLASSROOM - Rifqi, Muhammad Surya (English Department, University of Riau Kepulauan, Batam,Indonesia, 2023)
This study purposes to explore the challenges faced while implementing differentiated instruction in the context of an English foreign language classroom. A qualitative case study is utilized in this study to investigate the challenges encountered while adopting differentiated instruction in the context of an English foreign language classroom. The researcher employed a purposive sample method, selecting five participants who had engaged in differentiated instruction professional development and had experience implementing differentiated instruction. The study discovered that teachers face challenges when organizing and delivering differentiated instruction, such as dealing with the selection of materials, methods, and assessments that match students' characteristics, teachers' intrinsic factors, a large number of students, time invested, and learning references. Participants offered suggestions and feedback to other teachers who want to use differentiated instruction by exploring more variations of learning activities, being open to technology, participating in various forms of professional development, recognizing the personality of the students they teach, and spending more time preparing instruction so that student's learning needs are truly met. In order to get a more comprehensive understanding of differentiated instruction, the researcher recommends involving a greater number of participants, including teachers as well as students, in future studies.